Influence of chemicals and crude plant materials as pre-storage treatment on seed quality of onion (Allium cepa L.) (Bangladesh Journal of Agriculture, 2023)
Fresh onion seeds dried to 7.0% seed moisture content were stored with crude plant materials (red chili powder@20g/kg of seed; neem leaf powder@ 20g/kg of seed, lemon leaf powder @ 20g/kg seed), and chemicals (common bleaching powder and mancozeb @ 2g/kg of seed). The germination potential of onion seeds was found satisfactory in treated seeds. Water uptake during imbibition was maximum in lemon leaf treated seed which indicates better germination as the imbibition of water is an essential part of germination. A high correlation between EC measurements and germination was found; which indicates that conductivity readings have the potential to provide a rapid assessment of standard laboratory germination. In terms of seed-associated pathogens during storage, chemicals have shown better results in suppressing pathogens.Bangladesh J. Agri. 2023, 48(2): 54-62